Negative-sequence current filter based on inductance coils - Kletsel, Mark; Mashrapov, Bauyrzhan; Mashrapova, Rizagul; Kislov, Alexandr (Institute of Advanced Engineering and Science, 2025)
The construction of new relay protection systems without the use of current transformers is a fundamental problem of electro energetics, which has not yet been solved. This works suggests a negative-sequence current filter which receives information from inductance coils (ICs) mounted at a safe distance in the magnetic field of phase currents. This filter does not require current transformers, thus saving high-quality copper, steel, and expensive high-voltage insulation in amount unprecedented for relay protection (a 6 to 110 kV current transformer has 19 to 480 kg in weight). A circuit (including functional diagnostics) and a technique for selecting the parameters of filter components and the points where ICs should be fixed are presented; a structure for IC fastening is described. Computer simulation and experiment were used for data collection. The data show that i) the filter conversion coefficient m= 1.6, and imbalance increases by 7% at the network frequency f= 48–52 Hz; ii) protections based on this filter should have a time delay; iii) the filter is not inferior to well-known well-tested filters with current transformers; and iv) it is functional, but can only be used for single-standing electrical installations.